An Agile System to Enhance Productivity through a Modified Value Stream Mapping Approach in Industry 4.0: A Novel Approach - Varun Tripathi (MDPI AG, 2021)
Worldwide, industries are emphasizing the development of an agile system to sustain higher productivity, which can be applied to ensure improvements in all production conditions in industry 4.0. In the present scenario, several methods are used for improvements in production, such as value stream mapping, kaizen, just in time, Kanban, and total productive maintenance, etc., The objective of the present research article is to produce an agile system to sustain improvements in productivity through a methodology coupled with value stream mapping in industry 4.0. Value stream mapping is a lean-based method and is used for the maximization of productivity by the elimination of non-value-added activities. The proposed methodology has been validated by productivity enhancements achieved in a case study of the earthmoving machinery manufacturing sector. The study establishes that the proposed methodology would encourage industry personnel during decision-making processes, which would lead to improvements in production in industry 4.0.